Investigating the Effect of Pedestrian-Oriented Spaces on the Culture and Identity of Urban Spaces - Solatzadeh, Nasim; Baghaei, Azhang (Journal of History Culture and Art Research, 2017)
Abstract The presence of people in the city follows many cultural and social effects. The pedestrian-oriented spaces result in the presence of more pedestrians and hence increase cultural and social values; however, today with increasing cars, pedestrians are not considered more which significantly reduces the number of pedestrians walking in urban areas as well as cultural and social values. Pedestrians can also affect the urban identity. In this paper, the effect of pedestrians on the culture and identity of the city had been discussed. By investigating the current academic literature, studies concerning the pedestrians, urban space, culture and urban culture, identity and urban identity have been collected and finally, the effect of pedestrian-oriented spaces on the culture and urban identity have been discussed. Since, the historic fabric of the city is the symbol of identity, part of this study discussing successful pedestrians that had been made in historical context.